TRAINING NATURAL SCIENCE EDUCATION STUDENTS AS A PRE-SERVICE TEACHER IN CONSTRUCTING ASSESSMENT INSTRUMENTS OF COGNITIVE DOMAIN THROUGH CONSTRUCTIVIST CLASSROOM - Qurrotul Anfa (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2021)
This research aimed at training science education students as a pre-service teacher in constructing assessment instruments of cognitive domain through constructivist classroom. The modification of constructivist classroom in material of cognitive domain test assessment procedures was developed by researcher. The subject of this research were 22 college students semester V of natural science education students at STKIP Modern Ngawi. The research used pre-experimental design with one-shot case study design. The instruments used for analyzing the competences in constructing assessment instruments of cognitive domain was by students learning outcomes completeness sheet. The college students will be said to be complete their competences if they sufficient Criterion Referenced Evaluation specifically more than equal to 75%. Empirically, the result of this research according to the completeness of student learning outcomes as a whole was 85.50% or in a very valid category. It means that natural science education students can construct well assessment instruments of cognitive domain trough constructivist classroom.